IMPLEMENTASI PERATURAN WALIKOTA PEKANBARU NOMOR 15 TAHUN 2023 TENTANG PENYELENGGARAAN REKLAME DI KOTA PEKANBARU TAHUN 2024 - Sinaga, Cindy Novitasari; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The management of advertisements is one form of public space regulation that plays an important role in supporting the increase of local revenue through advertisement taxes. In accordance with Pekanbaru Mayor Regulation Number 15 of 2023 concerning the Management of Advertisements as a guideline for regulating advertisements in Pekanbaru City. In its implementation, various problems are still found, such as unlicensed advertisements, installation of advertisements that do not comply with regulations, limited supervision, and coordination between regional apparatuses. This research uses the theoretical foundation of Policy Implementation according to George Edward III, which is a concept that explains the factors for success in implementing a policy, including communication, resources, disposition, and bureaucratic structure. This research method uses a descriptive qualitative approach. Data collection was carried out through interviews and documentation, using primary and secondary data. The research location is in Pekanbaru City. Data analysis was conducted using an approach that includes data collection, data presentation, and conclusion drawing. The results of this research indicate that policy implementation has not run optimally. This is evident from the still large number of unlicensed billboard advertisements or those whose IMB/PBG permits have expired, the installation of advertisements in locations that do not comply with provisions, and the increase in illegal advertisements due to the change in the licensing system from IMB to PBG. This condition is worsened by ineffective communication to the community, limited implementing resources, inconsistent officer disposition, and bureaucratic structure and inter-agency coordination that do not yet support maximum enforcement. As a result, the management of advertisements has not fully complied with the provisions of Pekanbaru Mayor Regulation Number 15 of 2023. Keywords: Policy Implementation, Advertisement Management, IMB/PBG